Hyperelastic hydrophobic aerogel oil absorption material as well as preparation method and application thereof

By preparing superhydrophobic gelatin aerogel oil-absorbing materials without the need for crosslinking agents, the problems of high cost, low efficiency and environmental pollution in the existing oil spill repair technology are solved, and efficient and environmentally friendly oil spill recovery effect is achieved.

CN119431871APending Publication Date: 2025-02-14CHINA UNIV OF PETROLEUM (EAST CHINA)

Patent Information

Application Number
CN202411356329.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing oil spill repair technology has problems such as high cost, low efficiency, environmental pollution and non-biodegradation of materials, especially the adsorbents have shortcomings in adsorption efficiency, recyclability and reusability.

Method used

Using a low-density, high adsorption capacity super-hydrophobic gelatin aerogel oil-absorbing material without the need for crosslinking agent, the super-elastic and hydrophobic material is prepared by combining gelatin with surfactant and methyltrichlorosilane. aerogel material.

Benefits of technology

Aerogel materials with low density, high adsorption capacity and strong oil-water selectivity are realized, which can effectively adsorb oil spills, and through simple extrusion recycling, it improves oil spill recovery efficiency and reduces the cost of handling oil spills. The material is biodegradable and has good environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005063701920000091
    Figure BDA0005063701920000091
  • Figure HDA0005063701930000011
    Figure HDA0005063701930000011
  • Figure HDA0005063701930000012
    Figure HDA0005063701930000012
Patent Text Reader

Abstract

A preparation method of a hyperelastic hydrophobic aerogel material comprises the following steps: (1) adding 2-5 parts of gelatin into every 100 parts of water, and heating and stirring until the gelatin is completely dissolved; (2) under a stirring condition, adding a surfactant into the gelatin aqueous solution obtained in the step (1), and continuously stirring and uniformly mixing; (3) stirring the mixed solution obtained in the step (2) at a high speed, so that a large number of microbubbles are generated in the solution, and the volume of the solution is enlarged by 3-9 times; (4) pouring the precursor solution obtained in the step (3) into a mold for freeze forming, and then freeze-drying in a freeze dryer to obtain gelatin aerogel; and (5) grafting silane to the surface of the aerogel obtained in the step (4) to obtain the hydrophobic aerogel oil absorption material. The aerogel oil absorption material is low in density, high in porosity, good in compression performance and large in oil absorption capacity and can be recycled, the recovery efficiency of spilled oil is greatly improved, and the treatment cost of the spilled oil is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomass aerogel oil-absorbing materials, and in particular relates to a preparation method and application of a superelastic and hydrophobic gelatin aerogel oil-absorbing material modified by methyltrichlorosilane. Background Art

[0002] In recent years, marine oil spill accidents caused by marine transportation and offshore exploitation of petroleum have occurred frequently, which not only cause waste of resources and economic losses, but also seriously threaten the marine ecological balance and human health. It is particularly important to develop a green and efficient oil spill remediation method.

[0003] At present, the technologies used for marine oil spill remediation include skimmers, in-situ combustion, adsorption, chemical dispersants and bioremediation. However, these methods also have some limitations. For example, skimmers have high labor costs and are greatly affected by weather conditions, in-situ combustion will cause air pollution, chemical dispersants themselves may be toxic to marine organisms and their application is limited, and the bioremediation process is slow and the remediation effect is restricted by environmental conditions. Among these technologies, adsorption has been considered an effective oil spill remediation method in recent years because of its many advantages such as simple operation, low cost and no secondary pollution. Different types of adsorbents have been used for oil spill remediation, including clay, activated carbon, molecular sieves, synthetic polymers, etc., but these materials still have limitations in adsorption efficiency, recyclability and reusability, which greatly hinders their large-scale application.

[0004] Aerogel is a typical three-dimensional porous material. It has attracted great interest due to its low density, high porosity, large adsorption capacity and good recyclability, and is considered to be one of the most attractive adsorbents. In recent years, a series of aerogels that can be used as adsorbents have been developed, such as silica aerogel, graphene aerogel, carbon nanotube aerogel, etc., but the shortcomings of complex processes, high costs and non-biodegradability have greatly hindered their promotion and application.

[0005] New biomass aerogels have attracted much attention due to their abundant and readily available raw material sources, biodegradability and high environmental benefits. However, the preparation process of these aerogel materials often requires the use of toxic cross-linking agents, which may cause secondary pollution to the environment. In addition, they absorb oil and water at the same time and lack oil-water selectivity, making it difficult to cope with large-scale oil spills. Therefore, in the context of sustainable development, it is necessary to develop an efficient and environmentally friendly oil spill removal technology.

[0006] CN105924686A discloses a bio-based polymer aerogel oil-absorbing material, which comprises firstly cross-linking the bio-based polymer with a cross-linking agent to obtain a precursor solution, then freeze-drying the precursor solution to obtain an aerogel, and finally grafting silane on the surface of the aerogel to obtain a hydrophobic bio-based polymer aerogel oil-absorbing material, the density of which is 3.8 to 23.1 kg / m3 The water contact angle is at least 117.8°, and the adsorption capacities for gasoline, paraffin oil, chloroform and crude oil are 30.5-109.0 g / g, 33.2-131.2 g / g, 58.2-163.0 g / g, and 24.7-95.8 g / g, respectively. After 50 cycles of gasoline adsorption extrusion, the retention rate of the adsorption capacity of the material is 43-99%.

[0007] CN106750384A discloses an aminosilane-modified nanocellulose aerogel, and its preparation method includes: 1) converting the nanocellulose suspension into a translucent colloid; 2) extruding the nanocellulose colloid into a spherical or short rod-shaped hydrogel; 3) converting the formed nanocellulose hydrogel into an alcohol gel; 4) obtaining the nanocellulose aerogel; 5) adsorbing the gaseous organic amine on the surface of the nanocellulose aerogel; 6) vacuum recovering the remaining organic amine catalyst; 7) chemically reacting the gaseous aminosilane with the nanocellulose aerogel; 8) vacuum recovering the unreacted aminosilane; 9) obtaining the corresponding aminosilane-modified nanocellulose aerogel. Advantages: 1) eliminating the solvent recovery and separation process encountered in the liquid phase modification process, simplifying the process of amino modification; 2) maintaining the original microscopic three-dimensional network structure of the nanocellulose aerogel, and improving the modified grafting density and uniformity; 3) the process is simple, efficient and low cost.

[0008] CN114805910A discloses a method for preparing a super hydrophobic and heat-insulating aerogel. The directional freezing method is used to make the aerogel have a layered / porous oriented structure, which gives excellent heat-insulating properties. The structure and performance are adjusted by changing the chitosan concentration. No aldehyde cross-linking agent is required, which is more environmentally friendly. The chemical vapor deposition hydrophobic modification enhances the water resistance of the material. The method is simple and environmentally friendly, time-consuming, and the obtained chitosan aerogel has low thermal conductivity and anisotropy. This anisotropic thermal conductivity makes it axially heat-insulated, radially heat-dissipating, and heat transfer is more uniform, preventing local heating from damaging the aerogel. Summary of the invention

[0009] The purpose of the present invention is to provide a method for preparing a super hydrophobic aerogel oil absorbing material which has low density, high adsorption capacity, is reusable and has strong oil-water selectivity and does not require an external crosslinking agent, in view of the shortcomings of the existing oil spill remediation technology, and an aerogel oil absorbing material prepared by the method.

[0010] The objective of the present invention is achieved through the following technical solutions:

[0011] A method for preparing a superelastic hydrophobic aerogel material comprises the following steps:

[0012] (1) Add 2-5 parts of gelatin to every 100 parts of water, heat and stir until it is completely dissolved;

[0013] (2) adding a surfactant to the aqueous gelatin solution obtained in step (1) under stirring, and continuing to stir and mix;

[0014] (3) stirring the mixed solution obtained in step (2) at high speed to generate a large number of microbubbles in the solution and increase the volume of the solution by 3-9 times;

[0015] (4) pouring the precursor solution obtained in step (3) into a mold for freeze molding, and then freeze-drying in a freeze dryer to obtain gelatin aerogel;

[0016] (5) Grafting silane onto the surface of the aerogel obtained in step (4) to obtain a hydrophobic aerogel oil-absorbing material.

[0017] The heating temperature in step (1) is 35-80°C, preferably 50-60°C; the heating method is water bath heating; the heating and dissolving time is 30-120 minutes, preferably 40-60 minutes.

[0018] The amount of the surfactant added in step (2) is 0.01-1 part, more preferably 0.03-0.5 part, most preferably 0.07-0.28 part; the surfactant is an organic sulfonate, preferably an alkyl sulfonate, most preferably sodium dodecyl sulfate (SDS).

[0019] The stirring speed in step (3) is 3000-100000 rpm, more preferably 10000-50000 rpm; the diameter of the microbubbles is 1-1000 μm, more preferably 20-300 μm; the stirring time is 1-30 minutes, more preferably 5-10 minutes; and the volume is preferably expanded by 5-7 times.

[0020] The freezing temperature in step (4) is -10°C to -30°C, and the freezing time is 6-24h; the freeze-drying time is 24-48h, and the freeze-drying temperature is -30°C to -50°C.

[0021] The grafting in step (5) utilizes chemical vapor deposition, and the silane is one or more of methyltrichlorosilane, trimethylchlorosilane, methyltriethoxysilane, and hexadecyltrimethoxysilane; the grafting amount of the silane is 0.2-2 parts, preferably 0.5-1 parts.

[0022] The steps of grafting silane by chemical vapor deposition are as follows: placing a container containing silane and the aerogel prepared in step (4) in a sealed vacuum dryer, and heating it to a temperature at which the silane vaporizes, so that it reacts with the aerogel, the vaporization temperature is 50-65°C, and the reaction time is 6-24h.

[0023] Another aspect of the present invention discloses a superelastic hydrophobic aerogel material prepared by the method.

[0024] Another aspect of the present invention discloses the use of the prepared superelastic hydrophobic aerogel material for the adsorption and treatment of marine oil pollution.

[0025] Based on common knowledge in the art, unless otherwise specified, the parts mentioned in this application refer to parts by mass.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The raw materials of the oil-absorbing material prepared by the present invention are widely available, cheap, easily available, biodegradable, and will not have a negative impact on the environment;

[0028] (2) The preparation process of the present invention is simple, and aerogel with a three-dimensional network structure can be efficiently prepared without adding a cross-linking agent, which is more environmentally friendly;

[0029] (3) The aerogel oil-absorbing material prepared by the present invention has low density, high porosity and good compression performance, so it has a large oil absorption capacity and can be recycled by simple extrusion, which greatly improves the oil spill recovery efficiency and reduces the cost of oil spill treatment;

[0030] (4) The aerogel prepared by the present invention is modified by silane and has strong hydrophobicity, so that the material has excellent oil-water selectivity. Therefore, regardless of whether the density of the oil is smaller than that of water, the aerogel oil-absorbing material has the ability to efficiently adsorb oil. The hydrophobic layer on the surface of the material is also beneficial to improving the oil absorption efficiency and enhancing the compression performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a 500 μm resolution scanning electron microscope (SEM) photograph of the gelatin aerogel material prepared in Example 1;

[0032] Figure 2 This is a 20 μm resolution scanning electron microscope (SEM) photograph of the gelatin aerogel material prepared in Example 1;

[0033] Figure 3 The wettability of the gelatin aerogel material prepared in Example 1;

[0034] Figure 4 This is a 500 μm resolution scanning electron microscope (SEM) photograph of the gelatin aerogel material prepared in Comparative Example 1;

[0035] Figure 5 This is a 20 μm resolution scanning electron microscope (SEM) photograph of the gelatin aerogel material prepared in Comparative Example 1;

[0036] Figure 6 The wettability of the gelatin aerogel material prepared in Comparative Example 1;

[0037] Figure 7 This is the wettability of the gelatin aerogel material prepared in Comparative Example 2. DETAILED DESCRIPTION

[0038] The present invention will be described in detail and completely below in conjunction with specific embodiments and drawings. The following embodiments are only used to exemplarily illustrate and explain the present invention, and should not be understood as limiting the scope of protection of the present invention. Those skilled in the art may make some non-essential improvements and adjustments to the present invention based on the above content of the present invention, which still fall within the scope of protection of the present invention.

[0039] The reagents used in the following examples are all commercially available and can be used directly without further purification.

[0040] In the following examples, the contact angle of the aerogel was tested by using a contact angle meter SDC-200S; the morphology of the aerogel was observed using a scanning electron microscope FEIQuantaFEG250; and the cyclic compression performance of the aerogel under 50% strain was measured using an electronic universal testing machine UTM4103.

[0041] The density of the aerogel in the following examples is calculated by measuring the mass and size of the aerogel; the adsorption capacity and porosity of the aerogel are measured by a gravimetric method, specifically by measuring and recording the initial mass m0 of the aerogel before oil absorption, then completely immersing it in the oil for 5 minutes to allow the adsorption process to reach equilibrium, then taking out the oil-saturated aerogel, leaving it in the air for 30 seconds to remove the oil attached to the surface of the aerogel, and measuring and recording the mass m1 of the adsorption-saturated aerogel.

[0042] The adsorption capacity of aerogels was calculated by the following formula:

[0043] C abs (g / g)=(m1-m0) / m0

[0044] The porosity of aerogel is calculated by the following formula:

[0045] η(%)=(m1-m0) / m1×100%

[0046] Example 1

[0047] A method for preparing superelastic gelatin aerogel comprises the following steps:

[0048] (1) Dissolve 3 g of gelatin in 100 mL of deionized water and heat and stir at 50°C and 500 rpm on a magnetic stirrer until the gelatin is completely dissolved;

[0049] (2) then add 0.21 g of sodium dodecyl sulfate (SDS) and continue stirring;

[0050] (3) The mixed solution was then stirred at high speed for 5 minutes using a movable high-speed stirrer to generate a large number of microbubbles in the solution and expand the volume of the solution to 700 mL;

[0051] (4) The solution was poured into a mold, frozen in a -20°C refrigerator for 12 h, and freeze-dried in a freeze dryer for 36 h to obtain gelatin aerogel;

[0052] (5) Using chemical vapor deposition, the gelatin aerogel obtained in step (4) and 1.0 mL of methyltrichlorosilane are placed in a sealed container and kept warm at 55° C. for 6 h. The gelatin aerogel is then taken out and further dried at 55° C. for 1 h to remove excess methyltrichlorosilane, thereby obtaining a hydrophobic superelastic gelatin aerogel.

[0053] The obtained superelastic hydrophobic gelatin aerogel was subjected to performance testing, and the test results are as follows:

[0054] Figure 1 and Figure 2 The following are scanning electron microscope images of the superelastic hydrophobic gelatin aerogel obtained in Example 1 at magnifications of 100 times and 2000 times, respectively. It can be seen from the figures that the interior of the aerogel has a continuous and rich three-dimensional mesh porous structure, and the surface of the aerogel is covered with a large number of fine particles and is relatively rough. This is because a layer of organic silane film is formed on the surface of the aerogel after hydrophobic modification. This film also increases the thickness of the aerogel pore wall, which is beneficial to improving the mechanical properties of the aerogel and providing structural support for the compression and release of the aerogel.

[0055] The contact angle of the superelastic hydrophobic aerogel is 131.6°; after ten cycles of compression, it can still maintain more than 90% of its elasticity, and its structure and chemical properties are stable, with good reusability.

[0056] Example 2

[0057] The amount of gelatin added in step (1) of Example 1 was adjusted to 2 g. Other parameters were kept consistent with those of Example 1 to obtain a hydrophobic gelatin aerogel.

[0058] Example 3

[0059] The amount of gelatin added in step (1) of Example 1 was adjusted to 4 g. Other parameters were kept consistent with those of Example 1 to obtain a hydrophobic gelatin aerogel.

[0060] Example 4

[0061] The amount of gelatin added in step (1) of Example 1 was adjusted to 5 g. Other parameters were kept consistent with those of Example 1 to obtain a hydrophobic gelatin aerogel.

[0062] Example 5

[0063] The amount of SDS added in step (2) of Example 1 was adjusted to 0.07 g, and other parameters were kept consistent with Example 1 to obtain a hydrophobic gelatin aerogel.

[0064] Example 6

[0065] The amount of SDS added in step (2) of Example 1 was adjusted to 0.14 g, and other parameters were kept consistent with Example 1 to obtain a hydrophobic gelatin aerogel.

[0066] Example 7

[0067] The amount of SDS added in step (2) of Example 1 was adjusted to 0.28 g, and other parameters were kept consistent with Example 1 to obtain a hydrophobic gelatin aerogel.

[0068] Example 8

[0069] The volume of the solution in step (3) of Example 1 was adjusted to 300 mL, and other parameters were kept consistent with Example 1 to obtain a hydrophobic gelatin aerogel.

[0070] Example 9

[0071] The volume of the solution in step (3) of Example 1 was adjusted to 500 mL, and other parameters were kept consistent with Example 1 to obtain a hydrophobic gelatin aerogel.

[0072] Example 10

[0073] The volume of the solution in step (3) of Example 1 was adjusted to 900 mL, and other parameters were kept consistent with Example 1 to obtain a hydrophobic gelatin aerogel.

[0074] Embodiment 11

[0075] The modification conditions in step (5) of Example 1 were adjusted to place the obtained gelatin aerogel and 1.0 mL of methyltrichlorosilane into a sealed container, and kept warm at 55°C for 9 hours. The gelatin aerogel was then taken out and continued to be dried at 55°C for 1 hour to remove excess methyltrichlorosilane. The other parameters were kept consistent with Example 1 to obtain a hydrophobic gelatin aerogel.

[0076] Example 12

[0077] The modification conditions in step (5) of Example 1 were adjusted to place the obtained gelatin aerogel and 1.0 mL of methyltrichlorosilane into a sealed container, and kept warm at 55°C for 12 h. The gelatin aerogel was then taken out and continued to be dried at 55°C for 1 h to remove excess methyltrichlorosilane. The other parameters were kept consistent with Example 1 to obtain a hydrophobic gelatin aerogel.

[0078] Example 13

[0079] The modification conditions in step (5) of Example 1 were adjusted to place the obtained gelatin aerogel and 1.0 mL of methyltrichlorosilane into a sealed container, and kept warm at 55°C for 24 hours. The gelatin aerogel was then taken out and continued to be dried at 55°C for 1 hour to remove excess methyltrichlorosilane. The other parameters were kept consistent with Example 1 to obtain a hydrophobic gelatin aerogel.

[0080] Embodiment 14

[0081] The modification temperature in step (5) of Example 1 was adjusted to 45° C., and other parameters were kept consistent with Example 1 to obtain a hydrophobic gelatin aerogel.

[0082] Embodiment 15

[0083] The modification temperature in step (5) of Example 1 was adjusted to 65° C., and other parameters were kept consistent with Example 1 to obtain a hydrophobic gelatin aerogel.

[0084] Example 16

[0085] The modification temperature in step (5) of Example 1 was adjusted to 75° C., and other parameters were kept consistent with Example 1 to obtain a hydrophobic gelatin aerogel.

[0086] Embodiment 17

[0087] The modifier in step (5) of Example 1 was adjusted from methyltrichlorosilane to methyltriethoxysilane to perform hydrophobic modification in step (5), and other parameters were kept consistent with those in Example 1 to obtain a hydrophobic gelatin aerogel.

[0088] The relevant performance test results of the aerogel oil-absorbing material are shown in the attached table.

[0089] Comparative Example 1

[0090] The operation is the same as in Example 1, except that step (5) is not performed, and a gelatin aerogel without hydrophobic modification is obtained.

[0091] Figure 4 and Figure 5 These are scanning electron microscope images of the gelatin aerogel obtained in Comparative Example 1 at magnifications of 100 times and 2000 times, respectively. It can be seen from the images that the interior of the aerogel has a continuous and rich three-dimensional mesh porous structure, and the surface of the aerogel is relatively smooth, not covered with a silane film, is not hydrophobic, and has a contact angle of 0°. After ten cycles of compression, the aerogel structure is destroyed and only 46% of its elasticity can be maintained.

[0092] Comparative Example 2

[0093] The other operations are the same as those in Example 1, except for step (5):

[0094] 0.1 mL of methyltrichlorosilane was dispersed in 10 mL of anhydrous ethanol to prepare a modifier, which was evenly sprayed on the surface of the aerogel. After spraying, the aerogel was placed in a well-ventilated environment and dried naturally at room temperature for 24 hours. Methyltrichlorosilane reacted with the surface of the aerogel to form a hydrophobic layer. Finally, the aerogel was dried at 55°C for 1 hour to remove excess methyltrichlorosilane to obtain a hydrophobic gelatin aerogel.

[0095] Figure 7 This is the contact angle measurement diagram of the gelatin aerogel obtained in Comparative Example 2, and the measured contact angle is 105.4°.

[0096] Comparative Example 3

[0097] (1) Dissolve 1.00 g of gelatin in 100 mL of deionized water and heat and stir at 50°C and 500 rpm with a magnetic stirrer until the gelatin is completely dissolved;

[0098] (2) Under stirring conditions, add 2.00 mL of 37% formaldehyde aqueous solution to the gelatin solution and adjust the solution pH to between 5 and 7;

[0099] (3) Pour the resulting mixed solution into a mold and allow to crosslink overnight at room temperature until the solution forms a gel. Wash the formed gel several times in deionized water to remove unreacted formaldehyde and other byproducts. After washing, age at room temperature for 24 hours to further enhance the stability of the gel.

[0100] (4) The aged gel was frozen in a refrigerator at -20°C for 12 h and freeze-dried in a freeze dryer for 36 h to obtain a gelatin-formaldehyde cross-linked aerogel.

[0101] (5) Using chemical vapor deposition, the aerogel sample obtained in step (4) and a small beaker containing 1 mL of methyltrichlorosilane were placed in a sealed container and kept in a vacuum drying oven at 55° C. for 12 h. The gelatin aerogel was then taken out and continued to be dried at 55° C. for 1 h to remove excess methyltrichlorosilane, thereby obtaining a hydrophobic gelatin-formaldehyde cross-linked aerogel.

[0102] The properties of the aerogel materials obtained in the examples and comparative examples were tested, as shown in Table 1.

[0103] Table 1

[0104]

[0105] Through the oil absorption performance test of the aerogel materials obtained in the examples and comparative examples, it can be seen that the aerogel obtained in the present invention has strong hydrophobicity and excellent oil-water selectivity. Therefore, regardless of whether the density of the oil is smaller than that of water, the aerogel oil-absorbing material has the ability to efficiently adsorb oil. The aerogel material has more excellent compression performance and can be gelled without adding toxic cross-linking agents, which has higher environmental benefits.

Claims

1. A method for preparing a superelastic hydrophobic aerogel material, comprising the following steps: (1) Add 2-5 parts of gelatin to every 100 parts of water, heat and stir until it is completely dissolved; (2) adding a surfactant to the aqueous gelatin solution obtained in step (1) under stirring, and continuing to stir and mix; (3) stirring the mixed solution obtained in step (2) at high speed to generate a large number of microbubbles in the solution and increase the volume of the solution by 3-9 times; (4) pouring the precursor solution obtained in step (3) into a mold for freeze molding, and then freeze-drying in a freeze dryer to obtain gelatin aerogel; (5) Grafting silane onto the surface of the aerogel obtained in step (4) to obtain a hydrophobic aerogel oil-absorbing material.

2. The method according to claim 1, characterized in that The heating temperature in step (1) is 35-80°C, preferably 50-60°C; the heating method is water bath heating; the heating and dissolving time is 30-120 minutes, preferably 40-60 minutes.

3. The method according to claim 1, characterized in that The amount of the surfactant added in step (2) is 0.01-1 part, more preferably 0.03-0.5 part, most preferably 0.07-0.28 part; the surfactant is an organic sulfonate, preferably an alkyl sulfonate, most preferably sodium dodecyl sulfate (SDS).

4. The method according to claim 1, characterized in that The stirring speed in step (3) is 3000-100000 rpm, more preferably 10000-50000 rpm; the diameter of the microbubbles is 1-1000 μm, more preferably 20-300 μm; the stirring time is 1-30 minutes, more preferably 5-10 minutes; and the volume is preferably expanded by 5-7 times.

5. The method according to claim 1, characterized in that The freezing temperature in step (4) is -10°C to -30°C, and the freezing time is 6-24h; the freeze-drying time is 24-48h, and the freeze-drying temperature is -30°C to -50°C.

6. The method according to claim 1, characterized in that The grafting in step (5) utilizes chemical vapor deposition, and the silane is one or more of methyltrichlorosilane, trimethylchlorosilane, methyltriethoxysilane, and hexadecyltrimethoxysilane; the grafting amount of the silane is 0.2-2 parts, preferably 0.5-1 parts.

7. The method according to claim 6, characterized in that The steps of grafting silane by chemical vapor deposition are as follows: placing a container containing silane and the aerogel prepared in step (4) in a sealed vacuum dryer, and heating it to a temperature at which the silane vaporizes, so that it reacts with the aerogel, the vaporization temperature is 50-65°C, and the reaction time is 6-24h.

8. A superelastic hydrophobic aerogel material prepared by the method according to any one of claims 1 to 7.

9. Application of the superelastic hydrophobic aerogel material as claimed in claim 8 in the adsorption and treatment of marine oil pollution.

Citation Information

Patent Citations

  • Amino silane modified nanocellulose aerogel preparation method

    CN106750384A

  • Preparation method of super-hydrophobic and heat-insulating aerogel

    CN114805910A

  • Biology base polymer aerogel oil absorption material and preparation method thereof

    CN105924686A

Cited By

  • Composite biomass aerogel oil absorption material and preparation method thereof

    CN121732120A